Natusers’ motivations and attitudes in urban green corridors: challenges and opportunities. Case study of the Parc Fluvial del Túria (Spain) - M. Alonso Monasterio; P. Alonso Monasterio; María José Viñals (Boletín de la Asociación de Geógrafos Españoles, 2015)
Texto resumen.